A new Hyphessobrycon (Characiformes: Acestrorhamphidae) from the Central Amazon basin, Brazil - Lima, Flávio C. T.; Silva-Oliveira, Cárlison; Oliveira, Claudio [UNESP]; Faria, Tiago C. [UNESP] (My University, 2025)
A new species of Hyphessobrycon is described from the region of the lower rioTapajós basin, state of Pará, and tributaries of the northern bank of the Amazon River from the rio Itapiranga basin westward to the lower rio Negro basin, states of Amazonas and Roraima, Brazil. The new species exhibits a color pattern consisting in a conspicuous single humeral blotch and a conspicuous caudal peduncle blotch, a pattern shared with several congeners. It can be diagnosed from those congeners by some other pigmentary features, and from some of them by maxillary teeth, and/or branched anal-fin rays counts, anal-fin morphology, and fin hooks arrangement in matures males. The new species is most similar morphologically to a non-congener, Hemigrammus schmardae, with which it was found syntopically at the lower rio Negro but can be distinguished from it by some color pattern features. An analysis based on the cytochrome c oxidase I gene indicates that the new species is closely related to Hyphessobrycon ericae.
Keywords: Barcoding; Hemigrammus schmardae; Hyphessobrycon ericae; rio Negro; rio Tapajós